Assessing the drivers of land abandonment in afforested land reform projects in the Gert Sibande-District in Mpumalanga Province, South Africa - Tshidzumba, Ratsodo Phillip (University of Pretoria, 2023)
Dissertation (MSc (Forest Management and the Environment)c)--University of Pretoria, 2023.